Analisis Framing Berita Kasus Polisi Smackdown Mahasiswa Di Tangerang Di Media Online Detik.Com - Selvia Melika; Aliasan; Ahmad Harun Yahya (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Framing Analysis of Student Police Smackdown Case News in Tangerang on Detik.com Online Media is the title of this research paper. An Indonesian news site called Media Detik.com. The way Media Detik.com produces and presents news about the stabbing of Tangerang Police students is an articulation of the problems in this thesis. The "smackdown" case carried out by police officers against students participating in a demonstration in front of the Tangerang Regency Government office is the source of data for this research. The news of the incident was disseminated through the internet publication Detik.com. Data and documentation are the data collection tools used by the author to complete this thesis. Primary and secondary data are the categories of data in question. Meanwhile, written archives from the Detik.com web publication published from October 13 to October 23, 2021 are the documentation. After data collection, it will be studied for framing. One component of the constructionist worldview is framing analysis. This paradigm has a unique stance towards the media, as well as the way it views the news texts that are created. The constructionist perspective sees the media from a different perspective. The media is not only a free medium, but also shapes reality with its own opinions, prejudices, and viewpoints. Framing refers to actions that help people interpret events or reality. The author uses Zhondang Pan and Koisicki's framing analysis model which includes four structures: syntactic, scriptic, thematic, and rhetorical. This thesis will be evaluated and then presented using a qualitative descriptive approach that aims to describe an event or events that occurred during field research on a violent incident involving a student in Tangerang ended in a family manner. The violent police officer received a 21-day sentence and was detained.